(untitled) (Journal of Human Sciences, 2021)
This work deals with the role of Fazan in the service of the Moroccan Hajj, and follows this role over a period of more than 150 years through two Journeies that have covered the geographical area of Fazan, each providing us with details about the visited areas and the conditions surrounding the pilgrims’ convoys as they move between the stations of Fazan countries. It Besides, provided us with important information about the geography and physical centers of the roads and provided us with images of the welcome of the residents around the roads to the pilgrims of Mecca, which gave us a living testimony of love and respect between the newcomers and the resident. The first journey of Aben Malih al- Qaisi who went out of the city of Marrakesh in 1040-1042 H/ 1630-1633M, and without his trip under the name Anas al-Sari and al-Sareb, and after than century and a half the Journey of Hajj al-Bashir al-Narthli, who left his city in 1204-1205 H/ 1789-1790M, this trip was revealed by researchers in the past decade to give us welcome opportunity to study Fazan countries and their role in the Moroccan pilgrim’s trips.